DEATH AS RESISTANCE IN MARIANNE KATOPPO’S RAUMANEN (1977) - Alwin Firdaus Wallidaeny; Teguh Prasetyo (Prodi Sastra Inggris UKI, 2026)
This paper aims to expand on the reading of suicide in Marianne Katoppo’s Raumanen (1977). Building from a long-established trope of female suicide in tragic fiction, the martyrdom was usually read as a form of loss or madness. However, using the synthesis of Elaine Showalter’s Gynocriticism and Hélène Cixous’ concept of écriture féminine to understand how women own their bodies through writing. I want to argue that by narrating her own life in the novel, Raumanen, the narrator, reclaims her own body and voice. Consequently, this reading will provoke a critical reading of how suicide in fiction, especially conducted by women.